Facial wrinkle categorization using Convolutional Neural Network - Čedomir Vasić (Dermatology Reports, 2024)
A tool for the detection and classification of wrinkles on the facial skin is always welcomed in the pursuit of tight and beautiful skin. If this tool involves the use of a state-of-the-art neural network and high-quality images, there is a high likelihood that it will be practical. Five thousand and ninety-eight images were categorized into four classes by a trained expert and prepared for neural network training. The task was to determine whether such prepared data could serve as good material for learning and whether they could provide sufficiently high accuracy in prediction. It was found that the answer to this question is positive.